Ecological Efficiency, Investment Opportunity Set, and Capital Structure: The Path to Sustainable Financial Performance - Salma Aqila; Ana Kadarningsih; Linda Ayu Oktoriza; Fakhmi Zakaria (Denasya Smart Publisher, 2026)
This research is motivated by the dual pressures faced by Indonesia’s energy sector in balancing the acceleration of renewable energy transition with the necessity to sustain solid financial results. This research examines the influence of ecological efficiency, investment opportunity set (IOS), and capital structure on financial performance of energy sector firms listed on the Indonesia Stock Exchange (IDX) during 2022-2024. A quantitative method was applied, using panel data regression on 129 firm-year observations from 43 companies selected through purposive sampling. Based on the Chow test, Hausman test, and Lagrange Multiplier test, the Common Effect Model (CEM) emerged as the most suitable estimation approach. The findings reveal that ecological efficiency does not significantly impact financial performance within the short-term observation window of this study, as its economic benefits follow a lagging effect pattern that has yet to materialize in immediate profitability. In contrast, IOS shows a positive and significant influence on financial performance, indicating that companies with greater investment opportunities allocate resources more effectively to enhance ROA. Capital structure negatively and significantly affect financial performance, suggesting that excessive debt reliance reduces profitability due to higher interest expenses and financial risk. Simultaneously, all variables significantly influence financial performance. The findings conclude that investment decisions and capital structure management are more immediate determinants of short-term financial performance, while ecological efficiency requires a longer time horizon to generate measurable economic value.